Localized melt-scan strategy for site specific control of grain size and primary dendrite arm spacing in electron beam additive manufacturing. (November 2017) - Raghavan, Narendran; Simunovic, Srdjan; Dehoff, Ryan; Plotkowski, Alex; Turner, John; Kirka, Michael; Babu, Suresh
Abstract: In addition to design geometry, surface roughness, and solid-state phase transformation, solidification microstructure plays a crucial role in controlling the performance of additively manufactured components. Crystallographic texture, primary dendrite arm spacing (PDAS), and grain size are directly correlated to local solidification conditions. We have developed a new melt-scan strategy for inducing site specific, on-demand control of solidification microstructure. We were able to induce variations in grain size (30 μm–150 μm) and PDAS (4 μm - 10 μm) in Inconel 718 parts produced by the electron beam additive manufacturing system (Arcam®). A conventional raster melt-scan resulted in a grain size of about 600 μm. The observed variations in grain size with different melt-scan strategies are rationalized using a numerical thermal and solidification model which accounts for the transient curvature of the melt pool and associated thermal gradients and liquid-solid interface velocities. The refinement in grain size at high cooling rates (>10 4 K/s) is also attributed to the potential heterogeneous nucleation of grains ahead of the epitaxially growing solidification front. The variation in PDAS is rationalized using a coupled numerical-theoretical model as a function of local solidification conditions (thermal gradient and liquid-solid interface velocity) of the melt pool. Graphical abstract: Image